An investigation into the information-seeking behaviour of professionals, working within the pharmaceutical manufacturing sector in Ireland. Issue 5 (12th April 2022) - Browne, Bernie; Martzoukou, Konstantina
Abstract : Purpose: This research aimed to investigate the information-seeking behaviour (ISB) and information needs of different professional groups within the pharmaceutical manufacturing sector in the Republic of Ireland (i.e. for what purpose information is acquired), the information sources professional groups use (including in-house documentation, regulations, industry guidelines, standards and colleagues) and the factors, which influence professional groups' choice of information sources. Furthermore, the research explored the perceived level of support that exists towards knowledge and information sharing. Design/methodology/approach: A quantitative non-experimental research design, comprising of a self-completion survey questionnaire, was used to examine a number of information-seeking variables: information triggers, information sources and source influencers as well as information sharing enablers. It was related to four professional tasks: process technology/process development, regulatory support and quality/compliance support and engineering. Findings: The research provides new insights into the ISB of pharmaceutical professionals working within a highly regulated and high-performance production environment, including a greater understanding of the context in which professional groups experience information needs. The levels of agreement observed in relation to employees' perception of information-sharing enablers indicated an overall positive level of information sharing. Research limitations/implications: The study points to largely echoed previous findings which suggest that individual work role associated tasks prompt particular information needs. Further to this, work role associated tasks have a bearing on information source selection. Pharmaceutical professionals engaged in positive levels of information and knowledge sharing, relying on procedures, other colleagues and internal documentation as information sources. The participants also indicated a high level of agreement in respect to the value of available subject matter experts as information-sharing enablers. Practical implications: Organisations should aim to create opportunities for adequate time to share information and organisational structures, facilitating an overall organisational culture of sharing. A focus on information sharing through forums, seminars, meetings and working groups could enhance information sharing, through the development of communities of practice. Social implications: Pharmaceutical professionals relied on trustworthiness and quality as professional' top information source-influencing factors. Furthermore, the study demonstrated that working within a high-performance, target-driven and time-constrained production environment brings a particular contextual impact, where frequent urgent information triggers are experienced. These contextual factors warrant further investigation. Originality/value: A paucity of information exists with respect to the ISB of professionals, working within the pharmaceutical manufacturing sector, which is a sector known for its high level of information use and production. This paper offered an original empirical investigation of the ISB of professionals, working within the pharmaceutical manufacturing sector in the Republic of Ireland, focussing on key professional tasks. The research also addressed the level of support available for knowledge and information sharing.